THE IMPACT OF FIGURE SKATING ON THE FUNCTIONAL STATE OF ATHLETES - Bilyalova Nigina (Modern American Journals, 2025)
Figure skating is a complex sport requiring complex coordination. This is due to the fact that skaters use skates with blades whose contact area with the ice is very small, and the ice itself is very hard and slippery. Skaters must perform a variety of complex ice maneuvers, including multi-rotational jumps, which can often be accompanied by landing errors and falls. Advances in the development of the sport are largely due to the results of scientific research. Therefore, athletes are required to develop a high level of precision, speed, stability, and comprehensive coordination of movements in time and space. The significant changes in figure skating that have occurred in recent years, along with the increased technical skill of skaters, require the development and scientific substantiation of new, more advanced methods for figure skating training.